Herding cats : the role of persuasion in political change and continuity in the Association of Southeast Asian Nations (ASEAN) - Tan, See Seng (2014)
The role that peer pressure plays in efforts by member nations of the Association of Southeast Asian Nations (ASEAN) in socializing a reluctant or recalcitrant member(s) toward a diplomatic posture or policy position has been noted but not systematically addressed in the existing literature. Given that the decision-making in ASEAN has traditionally been a consensus-based, political suasion is therefore the key modality through which ASEAN members develop shared perspectives and, where possible, ensure collective assent to an existing or emerging norm or position. Peer pressure is likely the only means available for ASEAN states to promote ‘voluntary compliance’ without contravening their institution's non-interference principle. Three historical developments are examined: Indonesia and the formation of ASEAN, the establishment of the ASEAN Charter, and the constructive engagement of Myanmar. In all three instances, force-based coercion did not play a role, but persuasion did.